Ferromagnetic resonance of spin-valves: the case of IrMn(150Å)/Co(50Å)/Ru(32Å) /NiFe(50Å) system - Tarazona Coronel, H. S. (2014)
In this work we study theoretically the ferromagnetic resonance in a spin-valve. For this purpose, we propose a phenomenological model for the density of Helmholtz free energy taking into account the magnetocrystalline anisotropy, shape anisotropy, interlayer exchange coupling and exchange bias. Considering this energy density we solve the Landau-Lifshitz equation in spherical coordinates and in the resonance condition. In this way, we obtain the dispersion relation and, as a consequence, the frequency versus the resonance field. These results are in good agreement with the literature. Additionally, we apply the model to the IrMn/Co/Ru/NiFe system and study the magnetic coupling interlayers, where the non-magnetic layer (Ru) has a thickness of 3.2 nm. The results indicate the existence of an antiferromagnetic coupling with a strength of couping of Jbl + 2Jbc = −4.3 erg/cm2.